End of induction treatment outcomes with a novel cyclophosphamide-based regimen for severe lupus nephritis: Single-center experience from South India - V Jayaprakash; T Dineshkumar; J Dhanapriya; D Rajasekar; R Sakthirajan; T Balasubramaniyan; Anila A Kurien; N Gopalakrishnan (Indian Journal of Rheumatology)
Background: Cyclophosphamide is commonly used along with pulse steroids for induction immunosuppression treatment of severe forms of lupus nephritis (LN). Renal outcome data for proliferative forms of LN treated with cyclophosphamide from the southern parts of Indian subcontinent are sparse. Subjects and Methods: It was an observational study done for 2 years. All patients with severe proliferative forms of LN were included. They were treated with fixed monthly single doses of 500 mg intravenous cyclophosphamide-based induction therapy along with pulse and oral steroids, as per protocol. Renal remission rates were assessed at the end of 6 months. Adverse events during the induction therapy were documented. Results: The study included 41 patients. Of them, 37 (90.24%) patients were female and 4 (9.75%) patients were male. Nephrotic syndrome was the most common renal presentation (53.66%). The most common histological class was Class IV A (75.61%). At the end of induction therapy, complete renal remission occurred in 31.7% of cases and partial remission in 34.14% of cases. Infections were the most common adverse events that occurred in 48.4% of cases. Conclusions: Renal remission was observed in 65.85% of cases. Fixed low-dose cyclophosphamide-based induction can also be given over a 6-month period. Younger age was a significant risk factor for poor renal outcomes. Failure to achieve renal remission was a risk factor for mortality.